2019
DOI: 10.3390/ani9100853
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare of Pig-Hunting Dogs in Australia

Abstract: Simple SummaryThe hunting of feral pigs utilising dogs is a common recreational activity in Australia. These dogs assist hunters to find, pursue, and restrain feral pigs. It is a legal activity in some states and territories of Australia while it is banned in others and is considered a controversial method of pest control. Scant information is available in the peer-reviewed literature regarding the welfare of dogs used in pig hunting. We conducted a review of the limited scientific literature on working dogs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 62 publications
(126 reference statements)
0
28
0
Order By: Relevance
“…Possibly due to smaller samples sizes of atrisk dogs in our study, there was no difference observed in the sex of the dog in relation to antigen seropositivity. Pig-hunting dogs are thought to receive minimal veterinary and preventative health care and often travel widely with their owners during hunting expeditions [20,21]. Pig-hunting dogs are generally robust, large breed, shortcoated dogs that live outdoors [20], increasing their risk of being bitten by mosquitoes and thereby developing canine heartworm disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Possibly due to smaller samples sizes of atrisk dogs in our study, there was no difference observed in the sex of the dog in relation to antigen seropositivity. Pig-hunting dogs are thought to receive minimal veterinary and preventative health care and often travel widely with their owners during hunting expeditions [20,21]. Pig-hunting dogs are generally robust, large breed, shortcoated dogs that live outdoors [20], increasing their risk of being bitten by mosquitoes and thereby developing canine heartworm disease.…”
Section: Resultsmentioning
confidence: 99%
“…Pig-hunting dogs are thought to receive minimal veterinary and preventative health care and often travel widely with their owners during hunting expeditions [20,21]. Pig-hunting dogs are generally robust, large breed, shortcoated dogs that live outdoors [20], increasing their risk of being bitten by mosquitoes and thereby developing canine heartworm disease. Since they often reside close to pet dog populations, it will be important to investigate their potential as a reservoir for pet dogs sharing the same geography and receiving incomplete or lax canine heartworm preventative therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pigdogging is likely the most popular form of pig hunting in Australia (Orr et al, 2019). Young, white males from rural backgrounds are the dominant demographic of this expanding community, yet men living in urban/suburban areas are an emerging set of practitioners.…”
Section: A Brief Introduction To Pigdogging In Australiamentioning
confidence: 99%